ANALISIS KINERJA BADAN PENDAPATAN DAERAH KABUPATEN MANGGARAI BARAT MENGGUNAKAN METODE BALANCED SCORECARD - Agus Wahyudi; Dea Arem Tiara Harahap; Gregorius Antariksa Berybe (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
This study aim to analyze the performance of the Regional Revenue Agency of West Manggarai Regency is measured using the Balance Scorecard method both in the financial perspective, customer perspective, internal business process perspective, as well as learning and growth perspective. This research is a quantitative descriptive research with analytical tools for measuring performance through the balanced scorecard method, namely the customer perspective is measured by value for money, the customer perspective is measured by the community satisfaction index, the internal business process perspective is measured by the attributes of facilities and infrastructure, and the attributes of performance processes. then the learning growth perspective is measured by the attributes of motivation, the attributes of self-development opportunities, the attributes of innovation, and the attributes of the atmosphere at work. The results of the research show that the financial perspective which is assessed from the effectiveness shows that the average is not effective, then in terms of efficiency it shows that the average is efficient and from an economic point of view it is categorized as economical on average. The customer perspective shows the service quality value of West Manggarai Regency BAPENDA is categorized as B (Good). Furthermore, from the perspective of internal business processes, the attributes of Western facilities and infrastructure are in the good category, while the performance process attributes are in the very good category. Then from the growth and learning perspective, the motivational attribute is categorized as very good, while the opportunity attribute for self-development, innovation attribute, and working atmosphere attribute is in good category.